Strategy for increasing exports through ICT development and potential market mapping: Case study of Indonesia labor intensive industries - Akbar Pratama Kartika; Rossanto Dwi Handoyo (Global Business & Finance Review (GBFR), 2024)
Purpose: This research aims to specifically identify the role of ICT in the export performance of Indonesia's la-bor-intensive industries and Mapping potential market for Indonesia's labor-intensive industries export. Design/methodology/approach: The analysis was carried out by developing a gravity model and estimated using the Pseudo Poisson Maximum-Likelihood (PPML) and Generalized Method of Moment (GMM) methods as robust-ness tests. Findings: The estimation results show that ICT, both from the quantity aspect and the quality aspect, has a positive and significant impact on the volume of Indonesian exports. The results of this estimation have been proven to be consistent through several tests by controlling the problems of endogeneity, simultaneity, and auto-correlation. Research limitations/implications: The model developed in the study tends to interact with variables from both countries, namely Indonesia as an exporter country and a partner country for importing Indonesian products. The application of this kind of interaction causes the results of the interpretation to be unable to specifically explain the effect of variables in each country. Originality/value: This study discussed the impact of ICT through the quality and quantity aspects, this study also used product-level data, so the interpretation results more specifically explained the impact of ICT. Further analysis in this study also contributes significantly to identifying which partner has a potential market as the main destination of Indonesia's exports.
Keywords: 650; International trade; Labor-intensive industries; Gravity model; ICT; Internet; PPML; GMM